REPRESENTATION MATHEMATICS OF JUNIOR HIGH SCHOOL STUDENTS IN SOLVING TIMSS PROBLEMS IN TERMS OF GENDER - Teguh Santoso; Mokhammad Dedi Penta Putra; Rahmatia Rahmatia; Dwi Priyo Utomo (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2022)
The purpose of this study was to find out and describe the process of student representation in solving TIMSS cognitive domain questions in terms of gender. This study used descriptive qualitative method. This research was conducted at the Karangploso Islamic Middle School in Malang in class VIII in the odd semester of the 2021/2022 academic year. Data collection techniques in this study used tests and interviews. The data analysis technique used consisted of three stages, namely data reduction, data presentation and conclusion. The results of this study indicate that students with male and female gender in carrying out the process of representing questions in the cognitive aware domain do not experience problems, even though there are slight problems with male students in solving questions, students can still improve them. The process of representing material in the cognitive domain by female students is better than that of male students. Male students experience confusion in determining the initial steps when working on questions. While the process of representing questions in the cognitive reasoning domain, female students are also better than male students, female students are able to answer questions in the form of inequalities models well, while male students make mistakes in making inequalities models.